Effect of N, P, K Fertilizer Applications on Growth of Pinus caribaea Seedlings - Agrawal, D. C.; Rawal, S. K.; Bhatnagar, H. P. (Indian Forester, 1983)
Using a statistically laid 33 factorial design, the optimum N, P and K requirement for the growth of P. caribaea seedlings was determined under Glass House conditions. Four month old Pinus caribaea seedlings were grown in soil cultures and provided with urea (nitrogen source), superphosphate (phosphorus source), and muriate of potash (potassium source) Nitrogen at 336 kg/ha, phosphorus at 112 kg/ha and potassium at 336 kg/ha were the optimum N, P and K requirements to produce maximum height and diameter growth and biomass production. Since the soil used for experimentation was taken from the chir pine forest of Forest Research Institute, Dehra Dun, it is recommended that for the preparation of nursery beds for Pinus caribaea seedlings the soil should be supplemented with N, P and K levels as determined above.